Partner Relationships and Health: Marital Quality and Health Among Peri-Urban Ethiopian Couples. (31st August 2016) - John, Neetu A.; Seme, Assefa; Tsui, Amy O.
Abstract : The linkages between marital relationship quality (MRQ) and health are well established in the West, although mutual spousal influence on each other is underexplored. In the sub-Saharan African context, despite continued health challenges and changing marital structures, this research has been neglected. This study examined the influence of spousal MRQ domains — such as trust, commitment and conflict resolution — on each other's self-reported health over time, using two waves of data from 725 couples in peri-urban Ethiopia using the Actor Partner Interdependence Model. Although MRQ and self-rated health measures of wives and husbands were associated, these relationships were complex and gendered. While the wife's health rating had a positive influence on the husband's relationship quality, the husband's health ratings were negatively associated with the wife's relationship quality. Expanding knowledge on the role of spousal influence can broaden understanding of couple mechanisms that potentially promote positive health behaviours and protect the health of spouses in different settings.